Protocol to profile the bioenergetics of organoids using Seahorse - Ludikhuize, Marlies C. (STAR Protoc, 2021)
Addressing bioenergetics is key to evaluate the impact of metabolism on the regulation of biological processes and its alteration in disease. Organoids are in vitro grown self-organizing structures derived from healthy and diseased tissue that recapitulate with high fidelity the tissue of origin. Bioenergetics is commonly analyzed by Seahorse XF analysis. However, its application to organoid studies is technically challenging. Here, we share our in-house optimized protocols to examine organoid bioenergetics in response to drugs, gene knockdown, or to characterize the metabolism of specific cell types. For complete details on the use and execution of this protocol, please refer to Ludikhuize et al. (2020).